Islamic Governance and Inclusive Harmony: A Study of Minority Rights and Justice - Javad Ahmad Mir; Iqbal Malik; Shabir Ahmad Lone (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This paper explores the complex issue of social equality in Islamic states, with special focus on the role of minority rights in building peaceful and inclusive societies. Drawing on Islamic teachings, the study examines how different identities can coexist within a single social framework while maintaining justice and harmony. It engages with the ideas of scholars such as Abdul Aziz Sachedina, Beyza Tekin, and Abdullah Saeed, who have written extensively on justice, inclusion, and minority rights in Islam. The concept of “inclusive harmony” is presented as a social balance in which minority rights are not seen as favors, but as a natural and essential part of a just society. Using legal, philosophical, and sociological perspectives, the research analyzes laws, policies, and social attitudes in Islamic countries. Insights from Abdullah Ahmed An-Na’im on Islam and the secular state further help explain the challenges and possibilities of applying Islamic principles in modern governance. Overall, the study aims to offer a balanced understanding of diversity, justice, and inclusivity in Islamic societies.